Job Embeddedness dan Turnover Intention Pada Guru Honorer - Desi Salvina; Risana Rachmatan; Eka Dian Aprilia; Irin Riamanda (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2024)
The problems of honorary teachers are quite complex, including income problems, low trust in the organization and dissatisfaction at work. These problems can make honorary teachers have the desire to leave their jobs. The desire to leave a person's job is called turnover intention. One of the factors that can inhibit turnover intention is job embeddedness (work engagement). This study aims to examine the relationship between job embeddedness and turnover intention in honorary teachers. The subjects in this study were honorary teachers. The sampling technique in this study was accidental sampling with the number of participants being 270 honorary teachers. Data was collected using the Global Job Embeddedness Scale (GJES) and Turnover Intention Scale (TIS). The results of the analysis showed a significance value (p) = 0.000 (p0.05) with a correlation value (r) = -0.718 and a determination value of 51.5%. This shows that there is a negative relationship between job embeddedness and turnover intention in honorary teachers. Most subjects are in the category of high job embeddedness and low turnover intention. The benefits of this research can provide insights into the various factors that may encourage honorary teachers to remain in their jobs. By understanding the factors that make them feel connected to their work, educational institutions can develop more effective strategies in the future.Permasalahan guru honorer cukup kompleks di antaranya masalah penghasilan, rendahnya kepercayaan terhadap organisasi dan ketidakpuasan dalam bekerja yang dapat menyebabkan guru honorer memiliki keinginan untuk keluar dari pekerjaannya. Keinginan keluar seseorang dari pekerjaannya disebut turnover intention. Salah satu faktor yang dapat menghambat turnover intention adalah job embeddedness (keterikatan kerja). Penelitian ini bertujuan untuk melihat hubungan antara job embeddedness dengan turnover intention pada guru honorer. Subjek pada penelitian ini adalah guru honorer. Teknik pengambilan sampel pada penelitian ini adalah accidental sampling dengan jumlah partisipan sebanyak 270 guru honorer. Pengumpulan data dilakukan menggunakan Global Job Embeddedness Scale (GJES) dan Turnover Intention Scale (TIS). Hasil analisis menunjukkan nilai signifikansi (p) = 0,000 (p0,05) dengan nilai korelasi (r) = -0,718 dan nilai determinasi sebesar 51,5%. Hal ini menunjukkan bahwa terdapat hubungan yang negatif antara job embeddedness dengan turnover intention pada guru honorer. Mayoritas subjek berada pada kategori job embeddedness tinggi dan turnover intention rendah. Manfaat dari penelitian ini dapat memberikan wawasan mengenai berbagai faktor yang dapat membuat guru honorer bertahan di pekerjaannya, dengan memahami faktor yang dapat membuat mereka merasa terikat dengan pekerjaannya, sehingga nantinya institusi pendidikan dapat mengembangkan strategi yang lebih efektif.